Inequality and Opportunity The Relationship Between Income Inequality and Intergenerational Transmission of Income - Perez-Arce, Francisco (RAND Corporation, 2016)
The authors review recent trends in inequality in outcomes and opportunity and present evidence on their correlation across countries and within countries across time, then present a framework to understand the mechanisms underlying the relationship between inequalities in income and opportunity and discuss the potential effects of policies on opportunity and how these can be quantitatively assessed.